Effectiveness of Using Digital Quiz for Students in English Learning for Grade VI Elementary School Students - Non Norma Monigir; Mutia Harun; Fitria Mochtar (Departement of Mathematics Education, 2024)
This study aims to examine the effectiveness of using digital quizzes as Student Worksheets (LKPD) in English learning to increase student participation. The research method uses quantitative descriptive, this study was conducted at Elementary School 8 Tondano. The subjects of this study were 25 grade VI students. The research instrument used was a student response questionnaire on the use of Quiz in implementing wordwalls during class learning as many as 20 questionnaires. The results showed that most students (60.3%) strongly agreed with the use of quizzes in learning, which shows that this method is effective and beneficial for them. These results indicate that most students like the use of quizzes when studying. Quizzes that are tailored to the subject matter also allow students to test their understanding directly, increasing student participation and their understanding.